Patologija (ne)normalnog u drami Bolnica u doba revolucije Keril Čerčil (Philologia, 2023)
Caryl Churchill’s The Hospital at the Time of the Revolution is a documentary play based on Frantz Fanon’s psychiatric reports about the causes and nature of mental disorders, described in his books Wretched of the Earth and Black Skin, White Masks, as well as on Freud’s case study of Daniel Schreber, a judge diagnosed with paranoid schizophrenia who wrote about his illness in his own memoirs. The play relies on the anti-psychiatry model by R.D. Laing, who opposed repressive methods of the traditional psychology and psychiatry and defined neurotic disorders as alternative ways of understanding the world. The purpose of this paper is to offer an extensive analysis of the play that deals with the imperative issue of oppressive treatment of the other, be it in the strictly political terms of colonialized countries such as Algiers, or personal exploitation and suffocation of one’s individual self as in still popular authoritarian parenting.
Keywords: colonized; colonizer; illness; psychology; poisonous pedagogy; revolution